Prevalence and determinants of self-medication practice among selected households in Addis Ababa community. - Mensur Shafie; Mebrahtu Eyasu; Kedija Muzeyin; Yoseph Worku; Sagrario Martín-Aragón (PLoS ONE, 2018)
Self-medication (SM) is one part of self-care which is known to contribute to primary health care. If practiced appropriately, it has major benefits for the consumers such as self-reliance and decreased expense. However, inappropriate practice can have potential dangers such as incorrect self-diagnosis, dangerous drug-drug interactions, incorrect manner of administration, incorrect dosage, incorrect choice of therapy, masking of a severe disease, and/or risk of dependence and abuse. The main objective of this study was to assess the prevalence and determinants of the self-medication practice (SMP) in Addis Ababa.A community based cross-sectional study was conducted among selected households in Addis Ababa from April 2016 to May 2016, with a recall period of two months before its conduction. Trained data collectors were employed to collect the data from the 604 sampled participants using pre-tested and validated questionnaires.Among the 604 participants involved in this study, 422 (69.9%) were female and 182 (30.1%) were male and there was a mean age of 41.04 (± 13.45) years. The prevalence of SM in this study was 75.5%. The three most frequently reported ailments were headache 117 (25.7%), abdominal pain 59 (12.9%) and cough 54 (11.8%). The two main reasons for SM were mildness of illness 216 (47.4%) and previous knowledge about the drug 106 (23.2%). The two most frequently consumed medications were paracetamol 92 (20.2%) and traditional remedies 73 (16.0%), while drug retail outlets 319 (83.3%) were the main source of drugs. The two most frequently reported source of drug information were health professionals 174 (45.4%) and experience from previous treatment 82 (21.4%). Moreover, there were statistically significant differences among respondents who reported practicing SM based on income and knowledge about appropriate SMP.Self-medication was practiced with a range of drugs from the conventional paracetamol and NSAIDs to antimicrobials. Being that the practice of SM is inevitable, health authorities and professionals are highly demanded to educate the public not only on the advantages and disadvantages of SM but on its proper use.